The effects of wind and diurnal variability of surface heat fluxes on riverine thermal bar dynamics: a numerical experiment. Issue 3 (3rd July 2018) - Tsydenov, Bair O.; Starchenko, Alexander V.; Kay, Anthony
ABSTRACT: We numerically reproduced the spring riverine thermal bar in the area of the Selenga inflow into Lake Baikal using the nonhydrostatic 2.5D mathematical model. Our model took into account the diurnal variability of the heat fluxes and wind stress on the lake surface based on the atmospheric data from the Babushkin weather station archive during 1–30 May 2015. Propagation of the thermal bar is driven principally by the mechanical and thermal energy of the river inflow together with shortwave radiation while longwave radiation and latent and sensible heat fluxes make smaller contributions. Numerical modeling of the lake hydrodynamics demonstrated that the thermal bar propagation decelerated at night and that strong reverse motion of the thermal bar (toward the shore) was possible within some specific areas due to night cooling and opposing wind. These effects appear following an initial period in which the dynamics are dominated by the river inflow. As the distance from the mouth of the Selenga to the thermal bar increased, the impact of westerly winds on the reverse movement of the thermal bar was reinforced, although the influence of wind does not extend to the full depth of the lake.